Konsep Ketaatan Kepada Pemimpin Dalam Kebijakan Fiskal: Analisis Kenaikan Ppn 12% Menurut Pemikiran Aḥmad Al-Raisūnī : The Concept of Obedience to Leaders in Fiscal Policy: Analysis of the 12% VAT Increase According to the Thoughts of Aḥmad Al-Raisūnī - Gebrina Rizka; Muhammad Maulana; Muhammad Husnul (Journal of Indonesian Comparative of Syari'ah Law, 2026)
The government’s policy to raise the Value Added Tax (VAT) rate to 12%, as stipulated in Law No. 7 of 2021 on the Harmonization of Tax Regulations, has sparked public debate over its implications for economic justice and social welfare. This study aims to analyze the VAT increase through the lens of maqāṣid al-sharīʿah as conceptualized by Aḥmad al-Raisūnī, who emphasizes that public policy must be grounded in the principles of justice (al-ʿadālah), public welfare (al-maṣlaḥah al-ʿāmmah), and social responsibility. Using a descriptive-qualitative method and a normative approach through literature review, this research finds that fiscal policy is considered maqāṣidically legitimate only when it balances state revenue objectives with the protection of economically vulnerable groups. According to al-Raisūnī, citizens’ obedience to fiscal authority is conditional (ṭāʿah maqāṣidiyyah), valid only when governmental actions align with justice and the public good. Therefore, the legitimacy of the 12% VAT increase depends on its transparency, fairness, and tangible contribution to public welfare, ensuring that fiscal policy not only strengthens state finances but also upholds social equity and the moral purpose of governance envisioned in the maqāṣid al-sharīʿah framework.